Assessment of Nurses knowledge toward Postoperative Wound Care at Al-Diwaniya Teaching Hospital - Alaa Ebrahim Saeed; Batool Amin Jaddoue; Dergham Majeed Hameed (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: The study aims to assess nurse’s knowledge toward postoperative wound care also the discoverany link between sociodemographic characteristics concerning the knowledge nurses.Methodology: This cross – sectional descriptive design study was carried out with 1st of March 2020 to the1st of September - 2020. (70) staff nurses in surgical ward of Al Diwaniya Teaching Hospital. In order toassess the nurses’ knowledge about post-operative wound care. This staff who agreement to participate andwere recruited on giving oral consent .knowledge about postoperative wound care through (38) items thatdeals with .data was collected by distribution structure a self-administered questionnaire , these questionnairealso distribution on (11) experts .while finalized on the basis of the Test- retest reliability was determinedthrough a uses of Pearson Correlations. (r= 0.931**).Results: The outcomes of the search reveals, more than half nurses (54 %) at the age between 20 -28 yearsold. Concerning to gender results of study showed half of the study sample (50%) were female and (50%)of study sample were male. Most of them (60%) were single and reminder was married. Regarding to theireducational status, majority (50%) of the nurses was secondary nursing school degree holders, (28%) ofthe nurses had up to diploma nursing holder and( 22%) of the nurses were BSc degree holders. As regardtheir years of experience it was found that nearly three quarter of the nurses (72%) were5 to 10 years. Themajority of studied nurses (86%) had participated in training course. Twenty six (52%) of the nurses hadhigh level of knowledge regarding postoperative wound care, following by (30%) of total participants hadmoderate knowledge, finally few number of study participants (18%) were had poor knowledge. The findingof study demonstrated no relationship between awareness for nurse with sociodemographic variables.